Glucagon-Like Peptide 1 Receptor Agonists – Potential Game Changers in the Treatment of Glaucoma? - Mouhammad, Zaynab Ahmad; Vohra, Rupali; Horwitz, Anna; Thein, Anna-Sophie; Rovelt, Jens; Cvenkel, Barbara; Williams, Pete A.; Azuara-Blanco, Augusto; Kolko, Miriam (Frontiers in Neuroscience, 2022)
Glaucoma is a common ocular neurodegenerative disease characterized by the progressive loss of retinal ganglion cells and their axons. It is the most common cause of irreversible blindness. With an increasing number of glaucoma patients and disease progression despite treatment, it is paramount to develop new and effective therapeutics. Emerging new candidates are the receptor agonists of the incretin hormone glucagon-like-peptide-1 (GLP-1), originally used for the treatment of diabetes. GLP-1 receptor (GLP-1R) agonists have shown neuroprotective effects in preclinical and clinical studies on neurodegenerative diseases in both the brain (e.g., Alzheimer’s disease, Parkinson’s disease, stroke and diabetic neuropathy) and the eye (e.g., diabetic retinopathy and AMD). However, there are currently very few studies investigating the protective effects of GLP-1R agonists in the treatment of specifically glaucoma. Based on a literature search on PubMed, the Cochrane Library, and ClinicalTrials.gov, this review aims to summarize current clinical literature on GLP-1 receptor agonists in the treatment of neurodegenerative diseases to elucidate their potential in future anti-glaucomatous treatment strategies.